Paediatric follicular thyroid carcinoma – indolent cancer with low prevalence of RAS mutations and absence of PAX8–PPARG fusion in a Japanese population. Issue 5 (24th August 2017) - Vuong, Huy Gia; Kondo, Tetsuo; Oishi, Naoki; Nakazawa, Tadao; Mochizuki, Kunio; Miyauchi, Akira; Hirokawa, Mitsuyoshi; Katoh, Ryohei
Abstract : Aims: Paediatric follicular thyroid carcinomas are uncommon, and their clinicopathological features and molecular profiles are still unknown. In the present study, we aimed to investigate the clinicopathological aspects of a large series of follicular thyroid carcinomas (FTCs) in paediatric patients and to analyse the point mutations in codons 12, 13 and 61 of NRAS, HRAS and KRAS genes and the rearrangements of PAX8 – PPARG . Methods and results: A total of 41 paediatric FTCs less than 21 years of age were enrolled into the present study. We used direct sequencing and reverse transcription–polymerase chain reaction (RT–PCR) to detect RAS mutations and PAX8 – PPARG fusions, respectively. The paediatric FTCs were 6:1 in a female to male ratio, with a mean tumour size of 52.7 mm. Distant metastasis was found in one case at the time of presentation. During a median follow‐up time of 69 months, two cases had lung metastasis and all patients were alive. Histologically, all cases were minimally invasive FTCs and varied in growth patterns: microfollicular (39%), follicular (14.6%), solid/trabecular (6%), oncocytic (4.9%) and mixed patterns (26.8%). The mean Ki67 index was 5.7% and it was not statistically different among the growth patterns. NRAS mutations were found in five cases (12.2%) and associated significantly with small tumour size ( P = 0.014). PAX8 – PPARG fusion was not detected in our series. Conclusion: Paediatric FTCs are indolent in clinical course in spite of their large tumour size and have a distinct genetic background. RAS mutations and PAX8 – PPARG fusions may not play major roles in the tumorigenesis of paediatric FTCs.